Effects of Microencapsulated Synbiotic Administration at Different Dosages against heavy co-infection of White Spot Disease (WSD) and Vibrio harveyi in Pacific White Shrimp (Litopenaeus vannamei) - Yunarty Yunarty; Munti Yuhana; Widanarni Widanarni (Marine Science Department Diponegoro University, 2016)
White spot disease (WSD) is one of infectious disease in shrimp caused by white spot syndrome virus (WSSV). This study aimed to determine the dosage immunological effects and growth performances of microencapsulated synbiotic (Bacillus NP5 and mannan oligosaccharide) at different dosages on Pacific white shrimp. The microencapsulated synbiotic was administered as feed supplementation against the co-infection of WSSV and Vibrio harveyi. Synbiotic was encapsulated by spray drying method, further feed supplemented to Pacific white shrimp for 30 days at a dosages of 0.5% (A), 1% (B), 2% (C) and control treatments, i.e. without any microencapsulated synbiotic administration as positive control (D) and negative control (E). The challenge test was performed on day 30 after feeding supplementation, then the experimental shrimps were injected by WSSV intramuscularly at the infective dosage of 104 copies.-ml-1. Afterwards, 24 hours after WSSV injection the shrimps were immersed in water contained cells suspension of V. harveyi at the cells population dosage of 106 CFU-.ml-1. All synbiotic treatments showed better results with the values of Total Haemocyte Count (THC), Phenoloxidase (PO) and Respiratory Burst (RB), were higher (P<0.05) compared to positive control. The specific growth rates (SGR) of A, B and C showed higher than both controls of D and E. The feed conversion ratio (FCR) value of synbiotic treatments were lower (P<0.05) than both controls. However, the administration of microencapsulated synbiotic have not been able to prevent heavy impact of WSSV and V. harveyi co-infection due to lower SR and mortality pattern which continued to increase. Keywords: Synbiotic, Litopenaeus vannamei, WSSV, Vibrio harveyi, co-infection